The Design of New Adjuvants for Mucosal Immunity to Neisseria meningitidis B in Nasally Primed Neonatal Mice for Adult Immune Response - Tatiane Ferreira; Elizabeth De Gaspari (The Scientific World Journal)
The aim of this study was to determine the value of detoxified Shiga toxins Stx1 and Stx2 (toxoids of Escherichia coli) as mucosal adjuvants in neonatal mice for immunogenicity against the outer membrane proteins (OMPs) of Neisseria meningitidis B. Mucosal immunization has been shown to be effective for the induction of antigen-specific immune responses in both the systemic and mucosal compartments. Systemic antibody levels (IgG, IgG1, IgG2a, IgG2b, IgM, and IgA) and mucosal IgM and IgA were measured by ELISA using an N. meningitidis as an antigen. In addition, IFN-γ and IL-6 production were measured after stimulated proliferation of immune cells. Intranasal administration elicited a higher anti-OMP IgA response in both saliva and vaginal fluids. Our results suggest that both Stx1 and Stx2 toxoids are effective mucosal adjuvants for the induction of Ag-specific IgG, IgM, and IgA antibodies. The toxoids significantly enhanced the IgG and IgM response against OMPs with a potency equivalent to CT, with the response being characterized by both IgG1 and IgG2a isotypes, and increased IFN-gamma production. Additionally, bactericidal activity was induced with IgG and IgM antibodies of high avidity. These results support the use of the new toxoids as potent inducing adjuvants that are particularly suitable for mucosal immunization.